2015
DOI: 10.1002/jqs.2821
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene fluctuations of Quelccaya Ice Cap, Peru, registered by nearby lake sediments

Abstract: Records of clastic sediment from lakes that receive glacial meltwater provide a means for inferring past glacial fluctuations. However, increased clastic sedimentation has been interpreted to indicate both glacial advance and recession. Here we examine the timing of clastic sediment deposition in Challpacocha, a glacially fed lake located downvalley from Quelccaya Ice Cap (QIC), Peru, in comparison with known ice cap margin fluctuations. Using a comparison with a nearby non-glacial lake, Yanacocha, we document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Based on these data, we suggest that the Tributary I moraines mark the LMM ice extent at the Vilcanota site and that this occurred at <560 yr BP. Similar dates constrain the LMM at Quelccaya Ice Cap, confirming our findings (see section ‘Discussion’; Stroup et al, 2014, 2015).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Based on these data, we suggest that the Tributary I moraines mark the LMM ice extent at the Vilcanota site and that this occurred at <560 yr BP. Similar dates constrain the LMM at Quelccaya Ice Cap, confirming our findings (see section ‘Discussion’; Stroup et al, 2014, 2015).…”
Section: Resultssupporting
confidence: 89%
“…On the northwest side of Cordillera Vilcanota, in the Upismayo valley, Mark et al (2002) showed that the innermost moraine complex of the area was deposited after 340-560 cal yr BP (328 ± 46 14 C yr BP). In addition, at Quelccaya Ice Cap (15 km to the southwest of Vilcanota site), Stroup et al (2014Stroup et al ( , 2015 showed that the LMM in the Qori Kalis and Chalpacocha valley occurred at >520 ± 60 yr BP. Similar results were obtained by Phillips et al (2016), who constrained the LMM in the adjacent Huancané valley between 670 and 410 yr BP.…”
Section: Chronology Of the Lmmmentioning
confidence: 99%
“…They are not intended for use as accurate exposure ages, but instead are used to examine the age differences between adjacent and nearby surfaces. However, the CH‐2‐Unit‐2 record contains clastic rich (∼95%) sediment, which suggests higher meltwater production and an increase in subglacial erosion, corresponding to the beryllium‐indicated QIC retreat from 1490 to 1710 CE (Stroup et al., 2015). The monitoring of Qori Kalis has been discussed in several studies (Brecher & Thompson, 1993; Hanshaw & Bookhagen, 2014; Kelly et al., 2015; Lamantia, 2018; Stroup et al., 2014; Thompson et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies of the QIC detail a variety of methods that have been utilized to investigate the ice cap's past extent. These include radiocarbon dating of organic material found in sediment (Kelly et al., 2012), radiocarbon dating of vegetation remains (Buffen et al., 2009), cosmogenic nuclide surface exposure age dating ( 10 Be) (Kelly et al., 2015; Stroup et al., 2014, 2015), lake sediment records (Rodbell et al., 2008; Stroup et al., 2015), and paleo‐glacier reconstruction from moraine mapping (Mark et al., 2002; Mercer & Palacios, 1977). While many studies provide regional paleoclimate records from ice cores, moraines, and lake sediments (Rodbell et al., 2008; Stroup et al., 2015; Thompson, 2000), there are few precisely dated glacial landforms in the tropics (Kelly et al., 2015) which limits the understanding of glacier and ice cap behavior in response to changes in climate.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated amounts of organic matter were found in the MCA section of two lakes in the southern Peruvian Cordillera Central, Tarn Challpacocha (site 25) and Tarn Yanacocha (site 28) indicating MCA warming (Stroup et al, 2015) (Fig. S8).…”
Section: Andean Mca Productivity Boostmentioning
confidence: 99%